2010
DOI: 10.1039/b920411c
|View full text |Cite
|
Sign up to set email alerts
|

Substrate dependent structure of adsorbed aryl isocyanides studied by sum frequency generation (SFG) spectroscopy

Abstract: Effects of metal substrate on the bonding nature of isocyanide group of two aryl isocyanides, 1,4-phenylene diisocyanide (PDI) and 4-methylphenyl isocyanide (MPI), and tilt angle of MPI were examined by measuring sum frequency generation (SFG) spectra of the self-assembled monolayers (SAMs) of these molecules on Au, Pt, Ag, and Pd surfaces. The SFG peaks due to "metal bonded" and "free"-NC groups were resolved by comparing the SFG spectra of PDI with IR spectra obtained by DFT calculations and previous results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 69 publications
6
41
1
Order By: Relevance
“…67−71 Actually, our DFT calculations with PBE functional predicted the adsorption site of X−C6H4−NC molecule on the Pt(111) surface as the hollow site, although the experiment indicated that the molecule adsorbs at the atop site. 22 In the present calculation, N−C bond was oriented perpendicular to the Pt(111) surface, according to the experimental report. Figure 3 shows the top and side views of the optimized geometry of H−C6H4−NC molecule adsorbed on the Pt(111) surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…67−71 Actually, our DFT calculations with PBE functional predicted the adsorption site of X−C6H4−NC molecule on the Pt(111) surface as the hollow site, although the experiment indicated that the molecule adsorbs at the atop site. 22 In the present calculation, N−C bond was oriented perpendicular to the Pt(111) surface, according to the experimental report. Figure 3 shows the top and side views of the optimized geometry of H−C6H4−NC molecule adsorbed on the Pt(111) surface.…”
Section: Resultsmentioning
confidence: 99%
“…The C atom was positioned above one Pt atom, and the N−C bond was oriented perpendicular to the surface, which is consistent with the experimentally observed atop adsorption site. 22 Finally, the coordinates of the atoms in the bottom two layers were fixed while the adsorbed molecule and the upper two layers of the Pt surface were fully relaxed. Spin polarization was turned on in all calculations.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent work 32 showed similar frequencies of 2121 (free) and 2172 (surface-bound) cm -1 . Sum-frequency generation (SFG) results 4 found corresponding vibrational frequencies of 2122 and 2195 cm -1 . An average of the vibrational frequencies of isocyanide SAM's on gold (summarized in reference 4 ) results in values of 2123 ± 1 cm -1 for a free isocyanide group and 2181 ± 4 cm -1 for the surface-bound species.…”
Section: Discussionmentioning
confidence: 99%
“…Since the SFG intensity is proportional to | χ i j k ( 2 ) | 2 , the sign of the complex χ i j k ( 2 ) is lost in the conventional SFG spectra and, thus, difficulties are encountered in determining the absolute orientation of the molecules from the SFG spectra. As shown in Figure , by using substrates such as gold and silver, which can produce a certain nonresonant signal ( χ N R ( 2 ) ) under the SFG excitation conditions, one is able to obtain the phase information of χ i j k ( 2 ) by analyzing the interference between χ i j k ( 2 ) and χ N R ( 2 ) in the SFG spectra . However, this requires a special substrate, which is not always possible for the sample of interest.…”
Section: Molecular Structure Of Buried Interfacesmentioning
confidence: 99%